Optimalisasi Kemandirian Remaja Dalam Manajemen Kecemasan Melalui Pendekatan Mind Terapi Hiponisis Lima Jari Dalam Situasi Pandemi COVID-19 : Optimalisasi Kemandirian Remaja Dalam Manajemen Kecemasan Melalui Pendekatan Mind Terapi Hiponisis Lima Jari Dalam Situasi Pandemi COVID-19 - Ni Komang Sukraandini; Sang Ayu Ketut Candrawati; Ni Ketut Citrawati; Ni Ketut Ayu Mirayanti; Putu Gede Subhaktiyasa (Ahmar Metakarya: Jurnal Pengabdian Masyarakat, 2022)
Adolescence is a transition period from children to adults where at this time a person has an unstable emotional state in dealing with unexpected conditions, for example during this pandemic they feel excessive fear and anxiety about the transmission of the virus. Anxiety that lasts continuously, can cause disturbances to the physical and mental health of adolescents. Anxiety is one of the psychological conditions. This anxiety is also experienced by teenagers, because adolescence can be said to be an age that is still unstable in dealing with unexpected conditions. The emotional condition of adolescents will be easily shaken such as excessive anxiety, fear of contracting this virus and so on. Anxiety management is an effort to overcome disturbing anxiety but does not mean eliminating anxiety, but reducing it so as not to cause a person's obstacles in living their lives. However, anxiety management techniques in adolescents have never been done. Activities will be carried out with counseling related to anxiety and simulation of anxiety management techniques with five-finger hypnosis. The purpose of the activity is to increase the independence of adolescents, especially in managing the anxiety they feel. The results of the service carried out by using group discussion interview techniques showed that participants who took part in the activity felt calmer, more comfortable, and more understanding related to anxiety and how to reduce anxiety. Therefore, it is hoped that the activities of anxiety management techniques can be routinely carried out by adolescents so that they can reduce anxiety in adolescents.